Leonardo industrial designer - Taglialagamba, Sara (Incontri. Rivista europea di studi italiani, 2020)
Leonardo Industrial Designer Was Leonardo the first industrial designer? Leonardo tries to identify some matrices governing the extreme variety of things inside the whole. Such matrices are supposed to be archetypical entities which can be reproduced countless times in different ways, following geometric rules and standard proportions. We can therefore talk about a grammar of shapes that can be applied to several proportional rapports, symmetries and conceptual analogies which can generate concrete images of a stunning beauty. Leonardo was particularly keen on intertwining figures − dynamic matrices with a really high decorative potential. Leonardo makes use of twined and twisted shapes to describe very different phenomena. Matrix shapes consequently feature two different functions: they are used to investigate and better understand nature, and work as a precious tool for artistic and technical design. The decorations Leonardo creates by using them are therefore neither simple visual ornament, nor accessories to other works of art; on the contrary, they are fundamental and functional elements of a whole. Ornaments thus comply with the criteria of order, beauty and invention, which correspond to the definition of Industrial Designer formulated in the 20th century.